Chronic heart failure - Kearney, Mark (Oxford cardiology library., 2008)
Between 1-2% of the adult population have chronic heart failure, with 6-10% of people over the age of 65 years suffering from the disorder. While the age-adjusted incidence of chronic heart failure has remained stable over the last 20 years, its prevalence has increased with over one million cases in the United Kingdom alone. This practical pocketbook provides a guide for healthcare professionals - doctors, nurses and technical staff - who manage patients with chronic heart failure. Each chapter is written by a leader in that particular area of the treatment or investigation of chronic heart fa.